Frost and drought: Effects of extreme weather events on stem carbon dynamics in a Mediterranean beech forest. (20th September 2020) - D'Andrea, Ettore; Rezaie, Negar; Prislan, Peter; Gričar, Jozica; Collalti, Alessio; Muhr, Jan; Matteucci, Giorgio
Abstract : The cover image is based on the Original Article Frost and drought: Effects of extreme weather events on stem carbon dynamics in a Mediterranean beech forest by Ettore D'Andrea et al., https://doi.org/10.1111/pce.13858 .